Historical Foundations and Educational Practices in Greek Elementary Education: A Comprehensive Overview - Anastasopoulou, Eleni; Konstantina Lourida,; Evangelia Mitroyanni, (Technium Social Sciences Journal, 2024)
This paper provides an in-depth exploration of the historical factors shaping Greek elementary education and the contemporary pedagogical approaches and curriculum implemented in Greek elementary schools. Beginning with a historical analysis, the paper examines influential factors and developments spanning ancient times to the present day, including the legacy of ancient Greek education, Byzantine educational traditions, and modern educational reforms. By synthesizing historical insights with contemporary educational practices, this paper offers a holistic understanding of Greek elementary education. It underscores the enduring influence of historical legacies on present-day educational philosophies and methodologies while highlighting the innovative approaches adopted to meet the needs of modern learners. Ultimately, this comprehensive overview aims to contribute to scholarly discourse and inform ongoing efforts to enhance elementary education in Greece.